1998
DOI: 10.1046/j.1469-0705.1998.11060426.x
|View full text |Cite
|
Sign up to set email alerts
|

Doppler ultrasound evaluation of ductus venosus blood flow during acute hypoxemia in fetal lambs

Abstract: It has been demonstrated with invasive techniques in fetal lambs that the ratio of ductus venosus to umbilical vein blood flow rate (DV/UV ratio) increases during hypoxemia and infusion of catecholamines. Recently it was found in human fetuses using pulsed wave Doppler ultrasound equipment that the DV/UV ratio in fetuses with intrauterine growth restriction was significantly increased. The aim of the present study was to show in fetal lambs whether routine Doppler ultrasound devices were capable of determining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 14 publications
7
52
0
Order By: Relevance
“…Our finding is in agreement with published experimental studies (13,22). It has been shown that a comparable degree of fetal hypoxemia with our study caused a profound and immediate distension of the DV inlet (14,22).…”
Section: Discussionsupporting
confidence: 94%
“…Our finding is in agreement with published experimental studies (13,22). It has been shown that a comparable degree of fetal hypoxemia with our study caused a profound and immediate distension of the DV inlet (14,22).…”
Section: Discussionsupporting
confidence: 94%
“…The morphological evaluation and velocimetry of the DV during pregnancy has been described in humans and sheep [4,5,7]. Our study describes the DV in canine fetus and its main flow characteristics recorded using non-invasive Doppler sonography.…”
Section: Discussionmentioning
confidence: 99%
“…In this way oxygen can distribute preferentially to the fetal cardiac tissue and brain [4]. It was postulated that, during fetal hypoxia, over the 70 % of blood flow passing through the umbilical vein can shunt in the DV [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The problems with umbilical cord encompass its knots and many morphological abnormalities 21 . A true knot of the umbilical cord may lead to e. g. fetal hypoxia, intrauterine growth restriction and even to fetal death.…”
Section: Jan; 6(1):82-86mentioning
confidence: 99%